2013
DOI: 10.1074/jbc.m113.463059
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function Mutations in Transient Receptor Potential C6 (TRPC6) Activate Extracellular Signal-regulated Kinases 1/2 (ERK1/2)

Abstract: Background: Signaling events affected by disease-associated mutations in TRPC6 are poorly defined. Results: Expression of mutant TRPC6 induces ERK1/2 activation via both cell-autonomous and non-cell-autonomous mechanisms. Conclusion: Mutant TRPC6 activates complex signaling pathways that lead to the release of paracrine factors activating ERK. Significance: Understanding the signaling pathways downstream of gain-of-function TRPC6 is crucial for understanding TRPC6-mediated biology and pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 108 publications
5
41
0
Order By: Relevance
“…It has also been demonstrated that calpain 2 can be increased following Erk phosphorylation of serine 50. Further corroborating this possibility, recent evidence suggests that Erk phosphorylation is increased following glomerular injury (53). These results further emphasize the critical role of podocyte cell-matrix interactions in glomerular function in mice (2, 4), and humans (24,25) and how therapeutic targeting of these pathways may benefit patients (54).…”
Section: Discussionsupporting
confidence: 66%
“…It has also been demonstrated that calpain 2 can be increased following Erk phosphorylation of serine 50. Further corroborating this possibility, recent evidence suggests that Erk phosphorylation is increased following glomerular injury (53). These results further emphasize the critical role of podocyte cell-matrix interactions in glomerular function in mice (2, 4), and humans (24,25) and how therapeutic targeting of these pathways may benefit patients (54).…”
Section: Discussionsupporting
confidence: 66%
“…Hence, despite similar overall levels of intracellular calcium upon complement stimulation in control and wtTRPC6 or dnTRPC6 overexpressing podocytes, local TRPC6-dependent differences in intracellular calcium levels that escape detection using whole-cell calcium measurement might control spatially confined regulatory pathways. The ERK pathway is activated in response to complement injury (39) and has been implicated in TRPC6 effects on podocytes (40). We found prominent ERK activation in response to complement, but this activation was not dependent on TRPC6 (Fig.…”
Section: The Protective Potential Of Trpc6 In Complement Injury To Pomentioning
confidence: 50%
“…Recently, ERK signaling has been shown to be regulated downstream of TRPC6 [28,29,30]. Therefore, we examined whether TRPC6 mediates mesangial cell proliferation via ERK 1/2 in response to α 1 -AR stimulation.…”
Section: Resultsmentioning
confidence: 99%